ANALYSIS AND PROSPECTIVE UTILIZATION OF TECHNOGENIC SLAG WASTE FROM A LEAD PLANT - Z. Bagova; K. Zhantasov; G. Turebekova; B. Sapargaliyeva; Javier Rodrigo-Ilarri (Academic Scientific Journal of Chemistry, 2021)
The article presents the analysis and results of the study of technogenic slag waste of lead-zinc production. Slags of lead-zinc production contain a large number of toxic compounds: lead, zinc, osmium, cadmium, which are dangerous sources of environmental pollution. Due to the open storage of slags, it was found that the maximum permissible concentrations of lead were exceeded. Utilization of man-made slag waste is of great importance for reducing the negative impact on the safety of life and improving the environmental situation in the region. At the same time, slags are valuable raw materials containing compounds of non-ferrous and rare-earth metals. The article shows the results of laboratory studies of slags to determine the qualitative and quantitative composition of valuable components in the waste of lead production and the possibility of their further processing and disposal. Studies of the material of the heavy slag fraction were carried out on an electron probe microanalyzer of the JEOL IXA-8230 Electron Probe microanalyzer brand. X-ray diffractometric analysis of the average slag sample was performed on a DRON-4 diffractometer with Cu radiation, graphite monochromator. Samples were selected heavy fraction and manufactured artificial polished sections (briquettes). The sections were studied under the microscope of the brand LEICA DM 2500P and immersion in liquids. According to the results of research, it was found that lead slags contain a sufficiently high amount of nonferrous metal compounds: lead oxide up to 0.7 % and zinc oxide up to 8.5 % of the weight amount of slag, which makes the process of recycling toxic waste from lead production technically and economically feasible